Associação de terapia de fotobiomodulação e programas de exercícios na dor e incapacidade funcional de pacientes com dor lombar crônica inespecífica: uma revisão sistemática de ensaios clínicos randomizados - Penha, Thaise Fernanda Campos (2020)
Introduction: Photobiomodulation as a complement to exercise is common in clinical practice; however, the existing evidence for its recommendation is low. Therefore, the aim of this study was to determine whether photobiomodulation therapy provides additional benefits to exercise in patients with chronic non-specific low back pain. Material and methods: An electronic search was carried out in databases, including Medline via PubMed, EMBASE and Scopus, for randomized clinical trials published in English from 2003 to 2014. The selected studies were selected independently and the guidelines were used to describe this systematic review evaluated according to PRISMA (Preferred reporting items for systematic analysis and meta-analysis). Results: Six studies met the inclusion criteria for this review. Moderate evidence indicates that low- and high-level laser therapy provides additional short-term benefit for exercise in improving overall pain (10 cm visual analog scale of pain) and disability. Conclusions: Physiotherapists may consider the use of photobiomodulation therapy as a short-term supplement to exercise to improve pain in patients with chronic non-specific low back pain.